An integrative review on the shadow of abuse in pediatric head trauma - SÖNGÜT, Semra (Faculty of Medicine, Universitas Trisakti, 2025)
Introduction Abusive head trauma (AHT) is a significant public health issue that can lead to severe neurological damage or death in childhood. Often difficult to detect, AHT carries long-term consequences and requires high diagnostic vigilance. This integrative review aims to synthesize the current evidence on abusive head trauma in pediatric patients by identifying distinguishing diagnostic criteria, clinical patterns, and risk factors, in order to support early recognition, accurate diagnosis, and effective intervention strategies by healthcare professionals. Methods This integrative review aimed to systematically include studies published between 2020-2025 and the literature search was conducted in April-June 2025. The databases searched included PubMed and Web of Science. The keywords included in the search were